'n Strategiese bestuursbenadering tot sekuriteit en beheer binne 'n komplekse gerekenariseerde inligtingstelselomgewing - P. J.S. Bruwer (South African Journal of Business Management, 1991)
– A strategical management approach towards security and control within a complex computerized information system environment In a dynamic technological computer environment it is essential for management to establish a logical and systematic process to protect, secure and safeguard the management information resources and assets in such a manner to minimize risks, threats and exposures to a satisfactory and acceptable level. To achieve the objectives of total security implementation it is essential to identify the problems and factors (for example risks, threats and exposures) that might have an impact on computer security and control. It is necessary to define and understand computer security and control and important to assess the current situation to provide an implementation methodology to cover and enhance areas for improvement. In this research project a strategic management process approach is suggested to enable management to formulate and implement a strategy for security and control in a complex computerized information system environment.
Keywords: 650